Short-Term Effects of Sacubitril/valsartan on Echocardiographic Parameters in Dogs With Symptomatic Myxomatous Mitral Valve Disease - Saengklub, Nakkawee; Pirintr, Prapawadee; Nampimoon, Thanida; Kijtawornrat, Anusak; Chaiyabutr, Narongsak (Frontiers in Veterinary Science, 2021)
Background and objective: Sacubitril/valsartan (SV) is an angiotensin receptor-neprilysin inhibitor that works by inhibiting the neprilysin enzyme as well as blocking angiotensin receptors. The benefits of using SV in congestive heart failure patients has been demonstrated in several clinical trials; however, limited data are available for dogs with heart failure. The aim of this study was to investigate the short-term effects of SV in comparison with ramipril in the standard therapy of symptomatic dogs suffering from myxomatous mitral valve disease (MMVD). Methods: In this prospective, randomized, single-blind study, 21 dogs with MMVD stage C were randomly assigned to received SV (20 mg/kg orally twice a day) or ramipril (0.125 mg/kg, orally once a day) in addition to pimobendan and furosemide. Echocardiography, electrocardiography, blood pressure, N-terminal pro-B-type natriuretic peptide (NT-proBNP), and urinary aldosterone per creatinine ratio were obtained at baseline (D0) and at follow-up (4 weeks). Results: When comparing the percent change from baseline between groups, the left atrium to aortic root ratio (LA/Ao) and left ventricular internal diameter diastole normalized to body weight (LVIDDN) were significantly reduced in the SV group (P < 0.001 and P < 0.01, respectively). The end-diastolic volume index (EDVI), end-systolic volume index (ESVI), and stroke volume were lower in the SV group (P < 0.001, P < 0.05, and P < 0.01, respectively). No changes were observed between groups for NTproBNP, blood pressure, ECG parameters, and urinary aldosterone per creatinine ratio. Conclusion: The current study suggested that the short-term effects of SV can reverse myocardial remodeling, as inferred from several echocardiographic indices (i.e., the reduction in LA/Ao, LVIDDN, EDVI and ESVI) in dogs with MMVD stage C. These findings would support the use of SV in clinically symptomatic heart failure in dogs.